Human and digital ecosystems in the modern household - Pam Briggs; James Nicholson; Rhian Lukins (Frontiers in Psychology)
Despite a growing number of studies describing the digital ecosystems of the home, few have explored the human component of this ecosystem and fewer have accounted for household and relationship diversity. We asked the inhabitants of nine households to share images of their digital devices and then interviewed them about how the technology was distributed and used, what roles they adopted in relation to the different devices and what boundaries or rules they set up to manage joint use. Following a thematic analysis, we describe (i) the digital components of the ecosystem and their use; (ii) the humans in the ecosystem and their relationships with technology and with each other, and (iii) interconnectedness in terms of joint use and self- or other-imposed restrictions. We use this data to describe dimensions against which households will meaningfully differ and suggest how these dimensions might be used to explore the implications of household and relationship diversity for future smarthome technologies.